2015
DOI: 10.1128/jvi.01525-15
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of Interleukin-13/STAT6 Contributes to Kaposi's Sarcoma-Associated Herpesvirus-Related Primary Effusion Lymphoma Cell Proliferation and Survival

Abstract: Activation of the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signaling pathway has been associated with numerous human malignancies, including primary effusion lymphomas (PELs). PEL, a cancerous proliferation of B cells, is caused by Kaposi's sarcoma-associated herpesvirus (KSHV). Previously we identified constitutive phosphorylation of STAT6 on tyrosine 641 (p-STAT6C ) in PEL cell lines BC3 and BCBL1; however, the molecular mechanism leading to this activation remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
(66 reference statements)
2
24
0
Order By: Relevance
“…Previously, despite the absence of detectable phosphorylation of Y641 on STAT6 in KS tissue [24], we clearly observed there were more nuclear localization of total STAT6 in KS tissues than in normal skin controls (Fig 1A and 1B), which is further verified by the immunofluorescence assays against STAT6 and LANA (Fig 1C and 1D). To further confirm if infection of KSHV enhances nuclear localization of STAT6, endogenous STAT6 in iSLK cells with and without KSHV infection were monitored by immunofluorescence and cell fractionation assay.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Previously, despite the absence of detectable phosphorylation of Y641 on STAT6 in KS tissue [24], we clearly observed there were more nuclear localization of total STAT6 in KS tissues than in normal skin controls (Fig 1A and 1B), which is further verified by the immunofluorescence assays against STAT6 and LANA (Fig 1C and 1D). To further confirm if infection of KSHV enhances nuclear localization of STAT6, endogenous STAT6 in iSLK cells with and without KSHV infection were monitored by immunofluorescence and cell fractionation assay.…”
Section: Resultssupporting
confidence: 81%
“…In regards to STAT6, our previous studies have shown that KSHV blocks IL-4-induced STAT6 phosphorylation favoring latency, while stimulation with IL-4 resulted in RTA expression and reactivation of viral lytic replication [22,23]. We recently also found that KSHV retains a basal IL-13/STAT6 constitutive activation for cell survival and proliferation [24]. However, whether STAT6 plays a role in maintaining KSHV latency, independent of IL-4 or IL-13 stimulation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…LANA reduces IL-4-mediated phosphorylation of STAT6 on Y-641 and concomitantly its DNA binding ability (Cai et al, 2010a). However, STAT6 is constitutively activated in the PEL cells due to the secretion of IL-13 and downregulation of SHP1 by KSHV (Wang et al, 2015;Wang et al, 2017). Moreover, IL-13-stimulated constitutively phosphorylation of STAT6 is tightly associated with activation of JAK1 instead of PI3K and Akt (Wang et al, 2015).…”
Section: Virus Induces Cytokines Via Phosphorylationmediated Activatimentioning
confidence: 94%
“…However, STAT6 is constitutively activated in the PEL cells due to the secretion of IL-13 and downregulation of SHP1 by KSHV (Wang et al, 2015;Wang et al, 2017). Moreover, IL-13-stimulated constitutively phosphorylation of STAT6 is tightly associated with activation of JAK1 instead of PI3K and Akt (Wang et al, 2015). However, both IL-4 and IL-13 also activate STAT6 and induced by LMP-1 in EBV-infected B cells (Kis et al, 2011).…”
Section: Virus Induces Cytokines Via Phosphorylationmediated Activatimentioning
confidence: 98%
See 1 more Smart Citation